PENGARUH KEPRIBADIAN DAN PEMBERDAYAAN TERHADAP KINERJA MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN MODAL SOSIAL SEBAGAI VARIABEL MODERATING (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to analyze the influence of Personality and Performance through Empowerment against Organiztional Citizenship Behavior moderated by social capital Population Council Representative Officer at the National Family Planning Central Java Province. This research is expected to produce a useful analysis to provide empirical information about the influence of personality, empowerment, organizational citizenship behavior on employee performance with moderated social capital can be considered to            improvehumanresources.To examine the relationship between variables, the researchers used a technique Census, Data analysis using SPSS 20.00. Data were collected by using a questionnaire given to respondents study population 149 employees and entirely used as samples, while the samples were processed 118 respondents. Tests on research conducted by the test instrument validity (factor analysis) and coefficient alpha reliability test while statistical testing tool used is multiple regression analysis, t test, test and test R2 moderation. The results showed that personality positive and significant effect on OCB, Empowerment positive and significant effect on OCB, Personality positive and significant impact on employee performance, Empowerment positive and significant impact on performance, OCB positive and significant impact on employee performance, Personality no positive effect and significant impact on performance, Empowerment positive and significant impact on performance, OCB is not positive and significant impact on performance, test results showed that the OCB mediation mediate the effect of empowerment on employee performance, but OCB does not mediate the effect of personality on employee performance. The test results show that social capital moderation appropriately used as a moderating variable, which acts to moderate the relationship between empowerment employee performance. Keywords: Personality, Empowerment, OCB, performance and social capital